Evaluation of Iron Tablet Supplementation Program of Female Adolescent in Surakarta - Hardiningsih, Hardiningsih; Fatsena, Rizka Adela; Parwatiningsih, Sri Anggarini; Yunita, Freshy Astrika; Ropitasari, Ropitasari; Kartikasari, M. Nur Dewi; Hutomo, Cahyaning Setyo; Karimah, Nahdiyah Karimah; Pratiwi, Dyah Krisnawati Satia Pratiwi; Puriastuti, Emma Anastya (Universitas STRADA Indonesia, 2025)
Background: The 2021 Indonesian Nutritional Status Survey (SGI) found that the prevalence of stunting in Indonesia was 24.4%, exceeding the global prevalence of 22.2%. The prevalence of stunting in Central Java Province in 2022 was 20.9%. The percentage of stunted toddlers in Surakarta City in 2022 was 1.87%, an increase compared to 1.39% in 2021. Based on 2018 data from the Surakarta Health Office, the highest incidence of stunting was found at the Sangkrah Community Health Center (Puskesmas), at 3.35%. Stunting in children is often caused by inadequate nutritional intake for preconception adolescents during the first 8,000 days of life. One sign of inadequate nutrition is anemia in adolescents. Anemia can be prevented by regularly taking iron supplements (TTD) from adolescence. Purpose: To evaluate iron supplement administration among adolescent girls in Surakarta City. Methods: This study used a mixed-methods design. The study population was junior high and high school students in the Sangkrah Community Health Center (Puskesmas) area. Participants were 150 female students selected using cluster sampling. The first stage involved hemoglobin (Hb) testing and measuring the girls' knowledge and adherence to iron supplement administration using a questionnaire. The second stage involved focus group discussions (FGDs) with health workers from the Surakarta City Health Office, teachers, and junior high and high school students. Quantitative data were analyzed using product-moment correlation, while qualitative data were analyzed using thematic analysis. Results: The human resources involved in the iron supplement administration program at this school complied with the Anemia Prevention and Control Guidelines. The iron supplement distribution program has been implemented by the Surakarta City Health Office since 2022. Iron supplement distribution is carried out by 2-4 individuals. Most respondents in this study were compliant with iron supplement administration (73.3%). There was a significant relationship between iron supplement adherence and hemoglobin levels, with a p-value of 0.0001. Conclusion: The iron supplement program for adolescent girls has been running well. Monitoring is conducted by the Sangkrah Community Health Center every three months, and the majority of girls are compliant with iron supplement consumption.